FcRY is a key molecule controlling maternal blood IgY transfer to yolks during egg development in avian species - Okamoto, Mayuko; Sasaki, Ryo; Ikeda, Koki; Doi, Kasumi; Tatsumi, Fumiya; Oshima, Kenzi; Kojima, Takaaki; Mizushima, Shusei; Ikegami, Keisuke; Yoshimura, Takashi; Furukawa, Kyohei; Kobayashi, Misato; et al. (Frontiers in Immunology, 2024)
Maternal immunoglobulin transfer plays a key role in conferring passive immunity to neonates.Maternal blood immunoglobulin Y (IgY) in avian species is transported to newly-hatched chicks in two steps: 1) IgY is transported from the maternal circulation to the yolk of maturing oocytes, 2) the IgY deposited in yolk is transported to the circulation of the embryo via the yolk sac membrane. An IgY-Fc receptor, FcRY, is involved in the second step, but the mechanism of the first step is still unclear. We determined whether FcRY was also the basis for maternal blood IgY transfer to the yolk in the first step during egg development. Immunohistochemistry revealed that FcRY was expressed in the capillary endothelial cells in the internal theca layer of the ovarian follicle. Substitution of the amino acid residue in Fc region of IgY substantially changed the transport efficiency of IgY into egg yolks when intravenously-injected into laying quail; the G365A mutant had a high transport efficiency, but the Y363A mutant lacked transport ability. Binding analyses of IgY mutants to FcRY indicated that the mutant with a high transport efficiency (G365A) had a strong binding activity to FcRY; mutants with a low transport efficiency (G365D, N408A) had a weak binding activity to FcRY. One exception, the Y363A mutant had a remarkably strong binding affinity to FcRY, with a small dissociation rate. The injection of neutralizing FcRY antibodies in laying quail markedly reduced IgY uptake into egg yolks. The neutralization also showed that FcRY was engaged in prolongation of half-life of IgY in the blood; FcRY is therefore a multifunctional receptor that controls avian immunity.The pattern of the transport of the IgY mutants from the maternal blood to the egg yolk was found to be identical to that from the fertilized egg yolk to the newly-hatched chick blood circulation, via the yolk sac membrane. FcRY is therefore a critical IgY receptor that regulates the IgY uptake from the maternal blood circulation into the yolk of avian species, further indicating that the two steps of maternal-newly-hatched IgY transfer are controlled by a single receptor.